SHODHANA CHIKITSA AND STHANIK CHIKITSA IN STREE ROGA (AYUSHDHARA, 2018)
Healthy status of women is very much needed for society. In today's fast and competitive world, there is change in the lifestyle of women which leads to their physical and mental stress, women mostly gets affected by this environment and are prone to gynaecological problems. She always face many more very common health problem or gynaecological problem like white discharge, foul smell discharge, itching at vulval region, burning micturation etc., which are described detail in Stree rog vyadhi. As Ayurveda oldest system of health gives various Panchakarma and Sthanik chikitsa for such gynecologic problems and it gives an excellent result in above mentioned gynaecological problem. Sthanik chikitsa is cheap, easy, non surgical procedure. Anushastra Karma or parasurgical procedures means surgical procedure performed by non-surgical items or in absence of surgical instruments. Acharya Sushruta has described 60 Upkarma, 25 Upyantra and 14 Anushastra for the management of wound in different conditions. Shasti upkarma includes Kshara karma, Agni karma and Uttar basti etc., Kshar has given utmost importance and it is included under Shasti Upkarma upyantra and Anushastra, whereas Agnikarma is under Uyantra and Anushastra. Uttar basti is included under Shasti upkarma and Anushastra. Jaulaka is classified under Anushstra. Regarding Stree roga Yoni pichu, Yoni prakshalanam, Kshar karma, Uttar basti karma, are quite popular due to its excellent result and no adverse effect if followed properly.